Potentiation of U-937 cell differentiation by nitric oxide donors and assessment of heparanase as a differentiation marker. - Yamazaki, Amy. (University of Ottawa (Canada), 1996)
Our laboratory has been interested in the effects on leukocytes of reactive oxygen intermediates (ROI), such an superoxide (O$\sb2{\bar\cdot}),$ produced during the "respiratory burst". Upon stimulation, such cells employ the NADPH oxidase to reduce O$\sb2$ to form O$\sb2{\bar\cdot}$ using NADPH from the hexose monophosphate shunt (HMPS). In order to further study the effects of ROI, we planned to perform genetic manipulations on U-937 cells, a monoblastic cell line capable of differentiation into more mature leukocytes. In Part A, conditions to promote maximal U-937 differentiation into respiratory burst-competent cells were developed, thus allowing for such manipulations. Retinoic acid (RA) was found to be a potent inducer of a functional NADPH oxidase and HMPS, and of various mRNAs for their components. RA also reduced cell proliferation and altered cell morphology. The effects of RA were augmented by nitric oxide (NO$\cdot$) donors, believed to act by increasing intracellular cGMP levels. Among the NO$\cdot$ donors rested, only glyceryl trinitrate induced differentiation in the absence of RA. Since heparanase, an endoglycosidase which degrades heparan sulfate (HS), is active in mature leukocytes, the possibility that heparanase might serve as another U-937 differentiation marker was investigated. Because of a laboratory interest in cloning a heparanase cDNA based on enzymatic activity, Part B was devoted to the development of a heparanase assays for these purposes and for characterization of heparanases. A refined PAGE-based heparanase assay was used to test various cell types; KNRK cells were found to be the most active. Not previously characterized, KNRK heparanase was found to be a relatively stable enzyme with pH 6 optimum, inhibitable by heparin and able to digest a variety of HS substrates. Heparanase activity was virtually absent in immature U-937 cells and was only marginally increased during differentiation. Development of a more sensitive fluorescence-based heparanase assay was initiated.
Keywords: Biology, Cell.